The Effect of Adding Black Rice and White Rice on Rendement, Degree of Lightening, Antioxidant Activity of Coffee Powder and Organoleptic Properties of Coffee Drinks - Yustina, Ita; Abadi, F. R. (Proceedings of the International Conference on Green Technology, 2017)
Coffee is one of the plantation commodities that have high economic value among other plantation crops and plays an important role as a source of foreign exchange. Each region in Indonesia has a unique way of processing coffee beans into coffee powder, one of them by adding other ingredients such as rice. Therefore it is necessary to further investigate the effect of adding white rice to the yield and quality of coffee powder, as well as the potential of adding black rice as a mixture on the manufacture of coffee powder. The research was conducted in January - February 2017 at Pascapanen Mechanization and Technology laboratory of Assessment Institute for Agriculture Technology (AIAT) of East Java. The experiment design using Completely Randomized Design (RAL), the treatment consists of Pure Coffee (KM), Coffee + White Rice (KBP), and Coffee + Black Rice (KBH). Observation parameters consist of rendement, organoleptic properties, antioxidant activity. The results showed that the addition of black / white rice did not affect the yield, panelist's preference for color, bitter level of steeping coffee. However, the treatment had a significant effect on the degree of brightness (L) and antioxidant activity of coffee powder, panelist's preference for the flavour and taste. The addition of white rice or black rice causes the organoleptic properties likely flavour and taste of  KBH and KBP coffee drinks to be less favorable with score 3,18 (netral) for flavor and 3,55 (like) for taste, the color of the coffee powder becomes brighter (L KBH = 35), and increase the KBH antioxidant activity to 44.745%.